2018
DOI: 10.3390/molecules23061278
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein Electrophoretic Pattern in Neonatal Calves Treated with Clinoptilolite

Abstract: The objective of our study was to determine the effects of clinoptilolite supplemented in colostrum on the blood serum protein electrophoretic pattern of new-born calves. Methods: Romanian Black and White new-born calves involved in the study were divided into 3 groups: the control group (C) that received colostrum without clinoptilolite, and experimental groups I (E1) and II (E2) that received colostrum supplemented with 0.5% and 2% clinoptilolite, respectively. The concentration of total protein and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…The microvilli length was higher and the number of microvilli per square µm was higher (37), which could point to a better absorption capability. The other experiment with the newborn calves has demonstrated a better passive transfer of immunoglobulin into newborns (38).…”
Section: Discussionmentioning
confidence: 99%
“…The microvilli length was higher and the number of microvilli per square µm was higher (37), which could point to a better absorption capability. The other experiment with the newborn calves has demonstrated a better passive transfer of immunoglobulin into newborns (38).…”
Section: Discussionmentioning
confidence: 99%
“…Human serum contains approximately 60‐80 mg/mL proteins, of which about 50‐60% are albumins, and it is reported that PFOA and PFOS bind >99% of available human or bovine serum albumin 34,35 . This affinity for albumin which is present in the FBS at ~4.5 mg/mL protein and ~ 43 mg/mL protein in newborn calf serum 36 would sequester PFOS and PFOA in the media, effectively reducing intracellular availability of PFOA and PFOS in SSM treatments. While both higher than HFPO‐DA, PFOS and PFOA also displayed different trends in internal accumulation by dose.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,34 Human serum contains approximately 60-80 mg/mL proteins, of which about 50-60% are albumins, and it is reported that PFOA and PFOS bind >99% of available human or bovine serum albumin. 34,35 This affinity for albumin which is present in the FBS at 4.5 mg/mL protein and 43 mg/mL protein in newborn calf serum 36 which regulates trophoblast proliferation as well as angiogenesis, has been shown in both maternal serum and placenta to be inversely associated with preeclampsia. 43,44 In addition, pro-apoptotic markers BAD and BAX were up-regulated and anti-apoptotic BCL2 was downregulated in both SFM and SSM after exposure to PFOA, PFOS, or HFPO-DA.…”
Section: Discussionmentioning
confidence: 99%
“…Zeolites Applications in Veterinary Medicine DOI: http://dx.doi.org/10.5772/intechopen.87969 and 35.87%, p < 0.05, respectively) was reported, compared with the control group at 30 h postpartum, which indicates an obvious increase in globulin fractions in experimental groups. Clinoptilolite was effective in improving passive transfer in newborn calves, better if added in colostrum in a dose of 0.5% than in a dose of 2% (Figure 2) [67].…”
Section: Effects On Health Status and Growth Performancementioning
confidence: 99%